PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA KELAS XI IPS MATA PELAJARAN GEOGRAFI SMA NEGERI 2 PONTIANAK - Nurmala Nurmala; Nuraini Asrianti; Agus Sugiarto (Universitas Tanjungpura, 2022)
This research aims to determine the effect of online learning onstudents’ learning results in XI Grades of IPS at SMA Negeri 2Pontianak. The research method that used in this research is ex postfacto with a quantitative approach. The population that used in thisresearch were all students of XI Grades of IPS at SMA Negeri 2Pontianak which consisted of 185 students. The sample in this researchwas 65 students using a simple random sampling technique. Datacollection techniques used in this research were questionnaires anddocumentation. The results of this research showed that there was asignificant influence between online learning on students’ learningresults. Online learning results with an average score of 51.87 andstudents’ learning results with an average score of 56.35. Prerequisiteanalysis of online learning normality test results is 0.124 and learningresults are 0.280>0.05 can be declared normally distributed. Theresults of the linearity test are 0.302 > 0.05, so it can be stated that alinear in online learning on students’ learning results. Hypothesistesting, the results of simple regression analysis showed a sig score of0.001<0.05, a simple regression test can be said to predict variable Xin other words there is an effect of variable X on variable Y. Thesimple linear regression equation is Y = 22.58 + 0.651 X. The resultsof the determination test that the R2 of the online learning variable is0.163, which means that the online learning variable contributes16.3% to the effect of learning results.